Conceptual Study Of Enzymatic Wax Ester Synthesis In The Batch Reactor At Steady State And Isothermal Conditions - Ngu, Hung Hui (Universiti Sains Malaysia, 2021)
Wax ester is one of the most important ingredients with its many potential applications in the food industry, cosmetic industry, and pharmaceutical industry. Enzymatic esterification is preferable over chemical reaction due to its mild reaction and being more environmentally friendly. A mathematical model based on the mol balance in the batch reactor and Ping Pong Bi-Bi enzymatic rate equation was developed to study the kinetic parameter, thermodynamic parameter and operational parameter of enzymatic esterification in batch reactor. POLYMATH software (version 6) was used for the simulation of this mathematical model. The model was validated with experimental data obtained from literature sources while the values of certain parameters were estimated. From the validation, the experimental and theoretical data shows a good agreement (0.88 ≤ R2 ≤ 0.98) which proves that the model and the estimated kinetic and thermodynamic parameters are accurate to represent the actual process as R2 greater than 0.8. According to the findings and simulation results, a lower value of Km and ∆Gcat leads to a higher production yield as it indicates lower energy is required for substrate binding and to catalyze the reaction. On the other hand, a higher value of Ki and ∆Ginac are recommended for an enzyme because it indicates the enzyme is less affected by the inhibitor and resistance to deactivation at a higher temperature. Based on POLYMATH, optimum esterification conditions were 50°C temperature, 1.0×10-5 mol/L enzyme concentration and 1:2 fatty acid – fatty alcohol mole ratio. Profiling of enzyme is performed to study the inhibitory pattern. It found that, fatty alcohol shows more severe inhibition effect over fatty acid toward rate of reaction. Overall, my work on simulation is sufficiently adequate and has improved my understanding on the implementation of the production process on an industrial scale from laboratory scale.